Are the terms “creative accounting” and/or “earnings management” appropriate to describe the phenomenon of manipulations of accounting information? - Bachtijeva, Diana; Tamulevičienė, Daiva (Taikomoji kalbotyra, 2024)
The paper examines the essence of the phenomenon of manipulation of accounting information and the appropriateness of the terms “creative accounting” and “earnings management” to refer to it, and whether terms contribute to the misperception of this phenomenon. The aim of the study is to evaluate the impact of the terms “creative accounting” and “earnings management” used in the Lithuanian scientific and professional literature on the perception of the phenomenon of manipulations of accounting information. The study was carried out using an expert evaluation method. The results showed that the phenomenon of manipulations of accounting information was perceived by the experts as having a negative impact on accounting and accounting outcomes. However, when evaluating the terms used to describe this phenomenon, the experts pointed out that they have positive connotations. As the terms do not reflect the essence of the phenomenon being assessed, it is proposed to discontinue the use of these terms. Experts consider that the most appropriate term for this type of manipulations is “manipulative accounting”.
Keywords: creative accounting; earnings management; manipulations of accounting information; manipulative accounting; expert evaluation method; inconsistency in terms